Shipboard ECDIS cyber security : third-party component threats - Sviličić, Boris (Array, 2019)
The Electronic Chart Display and Information System (ECDIS) plays a central role in safe navigation of ships. The ECDIS is basically a software package running on a general operating system that could be comprised of the third-party components. This paper presents an analysis of cyber security weaknesses of a shipboard ECDIS raising from the ECDIS software’s third-party components. The analysis is based on the cyber security testing of the shipboard ECDIS using an industry vulnerability scanner. Detected vulnerabilities are analysed regarding the protection measures implemented on the ship. The results suggest that even the type approved ECDIS system with maintained ECDIS software and the underlying operating system could be vulnerable due to weaknesses in the ECDIS software’s third-party components.